2023
DOI: 10.1038/s41398-023-02576-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamus volume mediates the association between adverse childhood experience and PTSD development after adulthood trauma

Abstract: The hypothalamus is critical for regulation of the hypothalamic-pituitary-adrenal (HPA) axis and response to stress. Adverse childhood experience (ACE) can affect brain structure, which may contribute to development of posttraumatic stress disorder (PTSD) after subsequent adult trauma. It is unclear, however, if ACE history is particularly associated with aspects of hypothalamic structure which contribute to development of PTSD. To address this issue, the present study longitudinally assessed hypothalamic volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“… 27 However, concerning the effects of hormonal dysregulation resulting from stress, the literature reports that numerous evidences, 38 , 39 studies regarding possible neuroanatomical alterations of the hypothalamus in PTSD are still relatively scarce. However, a recent paper 40 analyzed by MRI the hypothalamic volume in adult subjects with a diagnosis of PTSD who had experienced one or more adverse childhood experiences (ACEs) during childhood, showing a significant reduction in this brain structure compared with that found in the control sample and subjects without PTSD. Volumetric reduction was particularly identified in the hypothalamic paraventricular nucleus (PVN).…”
Section: The Main Neuroanatomical and Functional Correlates Of Ptsdmentioning
confidence: 99%
“… 27 However, concerning the effects of hormonal dysregulation resulting from stress, the literature reports that numerous evidences, 38 , 39 studies regarding possible neuroanatomical alterations of the hypothalamus in PTSD are still relatively scarce. However, a recent paper 40 analyzed by MRI the hypothalamic volume in adult subjects with a diagnosis of PTSD who had experienced one or more adverse childhood experiences (ACEs) during childhood, showing a significant reduction in this brain structure compared with that found in the control sample and subjects without PTSD. Volumetric reduction was particularly identified in the hypothalamic paraventricular nucleus (PVN).…”
Section: The Main Neuroanatomical and Functional Correlates Of Ptsdmentioning
confidence: 99%
“…In postmortem studies of individuals with SCZ significant differences of the SON, PVN, or the SCN have not been observed, while a larger PVN volume was reported in an in vivo MRI study. 6 Some examples of the relationship between abnormalities in hypothalamic volume and impaired functioning, include: the size of the mammillary bodies was negatively correlated with negative symptoms and positively correlated with anxiety 7 ; a smaller right hypothalamus volume was associated with post-traumatic stress disorder symptoms, 34 which can be related to the HPA axis and consequently involve the ARC and PVN nuclei and stress-related molecular pathways; higher Body Mass Index was linked to larger subunit volumes, 35 potentially involving VMN nucleus, which regulates satiety and caloric intake.…”
Section: Introductionmentioning
confidence: 99%
“…To date, much of the functional neuroimaging research has been limited by examining single diagnoses, like depression or PTSD (9). Xie et al (10) found that reduced right hypothalamus volumes, as a reaction to childhood stress, may contribute to the development of PTSD in adult trauma survivors. Additionally, neuroimaging work has shown that larger amygdala volumes, as assessed by magnetic resonance imaging (MRI), are correlated with increased risk exposure during childhood (11).…”
Section: Introductionmentioning
confidence: 99%